FACTORS OF COMPETITIVE ADVANTAGE STRATEGY OF CAFE BUSINESS IN BANDAR LAMPUNG (STUDY ON DOESOEN CAFE BANDAR LAMPUNG) - Marcelina Shinta Wining Putri; Herry Goenawan Soedarsa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to identify strategic factors that are strengths, weaknesses, opportunities, and threats owned by Café Doesoen in Bandar Lampung. This is used as a basis for formulating internal and external environment analysis to develop appropriate competitive advantage strategies, using SWOT (Strength, Weakness, Opportunities, Threats) analysis techniques. Through analysis using this strategy provides an overview of how Doesoen Cafe can improve its competitiveness in the market segment of Bandar Lampung City. This research contributes to enriching the literature on competitive advantage strategies in the café industry, especially in Bandar Lampung City. In addition, the findings from this study can also provide valuable insights for other café business owners to develop effective strategies in the face of increasingly competitive competition.